2007
DOI: 10.1007/s00168-007-0140-8
|View full text |Cite
|
Sign up to set email alerts
|

Spatial externalities, neighbourhood rules and CA land-use modelling

Abstract: R14,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(43 citation statements)
references
References 24 publications
2
39
0
2
Order By: Relevance
“…This process has indirectly revealed the appropriateness of the selected variables involved in the land use changes in the vineyards. To this end, the Cohen (Cohen's Kappa) concordance index was used with success for its simplicity and clarity of interpretation (Carletta 1996;Hagoort et al 2008;Pontius 2000) through which the two compared maps have revealed a fair degree of conformity from both quantitative (number of pixels in the vineyard) and spatial points of view (i.e., checking the exact location of each pixel in both maps): two maps can have the same percentage of pixels for each class of land use, but different spatial allocations of these quantities. The study of spatial inconsistency is complex; it derives from a shift in position between pixels of different categories (Pontius and Schneider 2001).…”
Section: Validation Of Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This process has indirectly revealed the appropriateness of the selected variables involved in the land use changes in the vineyards. To this end, the Cohen (Cohen's Kappa) concordance index was used with success for its simplicity and clarity of interpretation (Carletta 1996;Hagoort et al 2008;Pontius 2000) through which the two compared maps have revealed a fair degree of conformity from both quantitative (number of pixels in the vineyard) and spatial points of view (i.e., checking the exact location of each pixel in both maps): two maps can have the same percentage of pixels for each class of land use, but different spatial allocations of these quantities. The study of spatial inconsistency is complex; it derives from a shift in position between pixels of different categories (Pontius and Schneider 2001).…”
Section: Validation Of Resultsmentioning
confidence: 99%
“…In the case of this work the rules of transition (refer to Introduction Section) of the geographic surfaces surrounding the study areas are considered. As stated by Hagoort et al (2008) the rules of transition consist of variables capable of driving the process of evolution of certain land uses which are determined based primarily on review of the literature and of interviews with industry experts. Furthermore, Hagoort et al (2008), in view of the possible influence of the territory on such variables, identify different types of functions relating to the variables on the basis of their distance from the land use in question.…”
Section: Areas Of Studymentioning
confidence: 99%
See 2 more Smart Citations
“…Then CA model provides transition/reclassification rules depending on the previous state and neighbourhood pixels of the current pixel under study. CA-Markov model evaluates multiple criteria and predicts the future change using probability matrices and reclassification rules [17,18,19]. The current study aims to assess landscape dynamics in the protected areas of Southern Karnataka.…”
Section: Introductionmentioning
confidence: 99%